12 sector dtc and pso-pi current control technics of z-source matrix converter for IM drive / Seyed Sina Sebtahmadi - Seyed Sina , Sebtahmadi (2016)
The first stage of this study investigates the sophisticated analysis of a novel switching strategy for a matrix converter (MC) based direct torque control (DTC) of an induction motor (IM) drive. The proposed switching paradigm utilizes twelve 30° sectors for both flux and voltage vectors. Analytical expressions of change rates of torque and flux for IM as a function of MC’s voltage vectors are derived. The influence of MC’s voltage vectors on the stator flux and electromagnetic torque variation is examined and an advanced switching scheme independent of any load and speed variation is developed. To decrease the switching losses of MC, the optimum switching state is selected by means of discretization and averaging on the flux variations. The performance of the proposed switching strategy is validated under rated conditions, and compared to the conventional hexagonal boundary switching scheme. In the proposed method, the characteristic of low torque ripples can be achieved with no need of rotational coordinate transformation and minimized switching frequency. The results verify that the degree of freedom to select proper voltage increases, and the torque ripple is hence significantly reduced up to 60% in comparison with the standard DTC method. The second phase of this study illustrates an IM fed by an Ultra Sparse Z-source Matrix Converter (USZSMC) under abnormal rate of input voltage, which reduces the THD of the output current by applying the intelligent method in the Particle Swarm Optimization (PSO) PI controller. The PSO method is employed to tune Kp and KI in the PI controller, and the coefficient of reference current and stator current. The practical topology of matrix converter has been improved by using only 9 semiconductor switches and 18 diodes. A Z-source network has been placed at virtual DC-link in order to boost up the voltage transfer ratio with the least number of passive elements. By applying any changes in reference current or frequency, the modulation index can be automatically adjusted and respond to changes without additional optimization or high computational requirements in the system. The merging above parts can bring the system a step forward to industries such aerospace. Since those advantage are the novelties of this research, which help us to have a simple, yet very cost effective and efficient system that can meet the requirements for industry. The concentration of this research is on reducing the torque ripple of IM, having a compact, light system with ability to meet the standards for industrial use with no extensive computing time. The promising simulation and experimental results have been presented to valide the proposed method.